Differential limbic–cortical correlates of sadness and anxiety in healthy subjects: implications for affective disorders - Liotti, Mario; Mayberg, Helen S; Brannan, Stephan K; McGinnis, Scott; Jerabek, Paul; Fox, Peter T (Biological psychiatry (1969), 2000)
Background: Affective disorders are associated with comorbidity of depression and anxiety symptoms. Positron emission tomography resting-state studies in affective disorders have generally failed to isolate specific symptom effects. Emotion provocation studies in healthy volunteers have produced variable results, due to differences in experimental paradigm and instructions. Methods: To better delineate the neural correlates of sad mood and anxiety, this study used autobiographical memory scripts in eight healthy women to generate sadness, anxiety, or a neutral relaxed state in a within-subject design. Results: Sadness and anxiety, when contrasted to a neutral emotional state, engaged a set of distinct paralimbic–cortical regions, with a limited number of common effects. Sadness was accompanied by specific activations of the subgenual cingulate area (BA) 25 and dorsal insula, specific deactivation of the right prefrontal cortex BA 9, and more prominent deactivation of the posterior parietal cortex BAs 40/7. Anxiety was associated with specific activations of the ventral insula, the orbitofrontal and anterior temporal cortices, specific deactivation of parahippocampal gyri, and more prominent deactivation of the inferior temporal cortex BAs 20/37. Conclusions: These findings are interpreted within a model in which sadness and anxiety are represented by segregated corticolimbic pathways, where a major role is played by selective dorsal cortical deactivations during sadness, and ventral cortical deactivations in anxiety.